Inclusive monitoring in the dentistry course in COVID-19 times: an experience report (Research, Society and Development, 2021)
Inclusive monitoring is understood as being a teaching and learning process that actively contributes to the integral formation of the undergraduate, focusing on the teaching, research and extension activities offered by the course. Given the above, this descriptive article, classified as experience report, has as its main objective to describe the experiences of inclusive monitoring carried out at the Federal University of Campina Grande. During the inclusive monitoring, the student was accompanied during the tests and activities, in addition to the weekly synchronous meetings. Therefore, it is important to make it clear that there was an exchange of knowledge with positive gains by both parties, being an indispensable experience for enabling the experience of pedagogical practices in a concrete way.